2017
DOI: 10.2166/wst.2017.199
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic numbers of granular activated carbon for the elimination of micropollutants from effluents of municipal wastewater treatment plants

Abstract: Adsorption on granular activated carbon (GAC) is a promising step to extend existing treatment trains in municipal wastewater treatment plants (WWTPs) and, thus, to reduce the concentration of micropollutants (MPs) (e.g. pharmaceuticals) in wastewater. It is common practice to use characteristic numbers when choosing GAC for a specific application. In this study, characteristic numbers were correlated for five different GACs, with measured adsorption capacities of these carbons for three pharmaceutical MPs (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…Previous studies have investigated the sorption characteristics of OMPs into GAC, in order to better predict the breakthrough of OMPs in GAC filtration [6,7]. Brunauer-Emmett-Teller (BET) (i.e., surface area, iodine number and aniline number) and the methylene blue number have been used to predict breakthroughs of OMPs [9,11], but they are not suitable markers for predicting the sorption of pharmaceuticals to GAC [9,12]. Mailler [13] studied six of the physical-chemical properties of 26 pharmaceuticals in a large-scale powdered activated carbon (PAC) pilot plant, using real wastewater, and found that the molecular charge of the pharmaceuticals was the most important property influencing adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the sorption characteristics of OMPs into GAC, in order to better predict the breakthrough of OMPs in GAC filtration [6,7]. Brunauer-Emmett-Teller (BET) (i.e., surface area, iodine number and aniline number) and the methylene blue number have been used to predict breakthroughs of OMPs [9,11], but they are not suitable markers for predicting the sorption of pharmaceuticals to GAC [9,12]. Mailler [13] studied six of the physical-chemical properties of 26 pharmaceuticals in a large-scale powdered activated carbon (PAC) pilot plant, using real wastewater, and found that the molecular charge of the pharmaceuticals was the most important property influencing adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Physico-chemical properties and chemical structure of selected contaminants of emerging concern (CECs). A commercial coconut shell-based GAC with high density value (520 ± 30 kg/m 3 ) was used as adsorbent in accordance with Benstoem et al [34]. In that paper, the authors described a high correlation between the high density of GAC sorbents and their capacity to adsorb CECs.…”
Section: Acetaminophen (Act) Nsaidsmentioning
confidence: 93%
“…Entries associated with lower SUVA and DOC values, in other words, DOM with more hydrophilic nature at a relatively low level of concentration would be susceptible to negative effect by increasing BET on BV10 prediction. This provides explanation as to why in single-solute isotherm experiments (Wu et al, 2005;Kearns et al, 2014) positive correlation between BET and MP removal was observed while in isotherm and column experiments with co-adsorbing DOM Benstoem and Pinnekamp, 2017), such correlation was absent. The presence of DOM adds complexity to the adsorption system and thus result in interactions between different parameters of the system, one of which is the combined interaction effect by SUVA and DOC (Figure 4d).…”
Section: Effect Of Carbon Characteristicsmentioning
confidence: 96%